Entre o direito dos povos e a justiça global: uma análise da concepção de direitos humanos de John Rawls - Vasconcelos, Renato Barbosa (2014)
The reiterated violations to human rights rules occurred in the XXI century indicate the valuation of these rights in the international sphere has not implicated their effective observance in the whole world. Discussing the challenges that must be overcome so that human rights be effective consists, therefore, in a fundamental step in order to avoid their rules´ support don´t be more than a mere rhetorical device. Based on that, this work intends to analyze if the human rights conception grounded in John Rawls´ theory of “justice as fairness”, is theoretically adequate to deal with problematic issues relating to semantic, culture and jurisdiction of those rights, demonstrating how that paradigm offers contributions to the solution or reduction of those problems.